Plant breeding reviews : Volume 33 - Janick, Jules, 1931- (Hoboken, N.J. : Wiley, 2009)
Plant Breeding Reviews presents state-of-the-art reviews on plant genetics and the breeding of all types of crops by both traditional means and molecular methods. Many of the crops widely grown today stem from a very narrow genetic base; understanding and preserving crop genetic resources is vital to the security of food systems worldwide. The emphasis of the series is on methodology, a fundamental understanding of crop genetics, and applications to major crops.
Frontmatter -- Color Plates -- Dedication: Kenneth J. Frey: Oat Breeder, Educator, and Champion of Plant Breeding / Ann Marie Thro, Larry Robertson -- Strategies for Enhancing Grain Yield in Maize / M Tollenaar, E A Lee -- Quality Protein Maize: Progress and Prospects / G N Atlin, N Palacios, R Babu, B Das, S Twumasi-Afriyie, D K Friesen, H De Groote, B Vivek, K V Pixley -- Vegetative Phase Change in Maize: Biotic Resistance and Agronomic Performance / M A Chandler, E S Riedeman, W F Tracy -- Plant Interspecific Hybridization: Outcomes and Issues at the Intersection of Species / Ed R Morgan, Gail M Timmerman-Vaughan, Anthony J Conner, William B Griffin, Richard Pickering -- DNA-Based Identification of Clonally Propagated Cultivars / Hilde Nybom, Kurt Weising -- Designing Marker-Assisted Inbred Line Development Strategies Using Computer Simulation / Guoyou Ye, M van Ginkel.
Includes bibliographical references and index.
Print version record.
Keywords: Plant breeding; Crops -- Genetics; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Crops -- Genetics; Plant breeding; Electronic books